DURASI ASIMILASI VOKAL TANWIN DALAM PEMBACAAN AL-QUR’AN SURAH AL- ISRA’ OLEH QARI’ INTERNASONAL - Sri Octaviyanti (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2023)
This study aims to analyze the duration of assimilation on tanwin vowel. The discussion studied in this study is the calculation of the duration of tanwin vowel assimilation. This study uses acoustic phonetic theory by applying qualitative descriptive methods through observation and data editing techniques. To analyze the data, there are four analytical techniques that are applied, namely the note-taking technique, the sorting technique, the digitization, and the sound segmentation. Meanwhile, for measuring the duration of the assimilation of sounds, this study used the praat program version 4.0.27. After the data analyzed, the results of the study showed that the duration of the reading of tanwin vowel assimilation by reciter 'DH sorted from the longest to the shortest, namely: For the duration of tanwin vowel assimilation read by reciter 'DH, from the longest duration lies to the shortest duration is seen in the word ʃaiɁĩn:faʂalnahu] has a duration of 3.171 md, the word [wa:ziratuw:wizra] has a duration of 2.448 md, the word [daraja:tiw:waakbaru] has a duration of 2.434 md, the word [xabi:ram:baʂi:ra] has a duration of 2.356 md, the word [faɖlam:min] has a duration of 2.186 md, the word [muɁminun:faɁula:Ɂika] has a duration of 2.029 md, the word [kita:bay:yalqahu] has a duration of 1.857 md, the word [maðmu:mam:madћu:ran] has a duration of 1.720 md, the word [kullan:numiddu] has a duration of 1.570 md, dan the word [ajraŋ:kabiran] has a duration of 1.287 md.